JQuery Game Development Essentials - Arsever, Selim (Packt Publishing, Limited, 2013)
Written as a concise yet practical guide with an explicit focus on utilizing jQuery for game development, you'll learn how to create stunning games that look great without the hassle of learning about a complex game engine in the process.Knowledge of JavaScript and jQuery as well as basic experience with frontend development is all you need to start making games in a matter of hours with this essential guide. Whilst also suitable for those who simply want to start making games with jQuery, it's specifically targeted at web developers that want to experiment with and utilize their existing skills.